Game Theory : A Critical Introduction / Shaun Hargreaves-Heap ; Yanis Varoufakis. - Hargreaves-Heap, Shaun, 1951- (Routledge, 1995)
Requiring no more than basic arithmetic, provides a careful and accessible introduction to the basic pillars of Game Theory, tracing it's intellectual origins and philosophical premises.